Specyfika komunikacji werbalnej i niewerbalnej dziecka z zespołem Aspergera w kontekście odgrywanej przez nie roli ucznia i kolegi - Gacka, Ewa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Communication is one of the most important elements of human existence, because man as a social being strives to communicate with others. Communication skills influence the degree of acceptance of the person by other members of the community and help to achieve success in various aspects of life and social roles. The article focuses on the analysis of communication skills, both verbal and non-verbal, of a child with Asperger syndrome (AS). The purpose of this article is to show the specific way in which people with Asperger syndrome communicate, which makes it difficult for them to find themselves in the school community – being a good pupil and a good colleague.